The Lord is here, and I did not know it: the revelation of the person and the person as revelatory in Walsh and Balthasar - Santamaria, Jerome (Tesi gregoriana, 2022)
This study considers the intersection of person and revelation. The revelation of the person of Jesus Christ is the heart of Christianity. Christian revelation therefore takes on a personal dimension. Likewise, the person of Jesus Christ is revelatory, and therefore persons must be understood in this light. Part One considers broadly both the concept of personhood and that of revelation as large areas of study drifting toward each other. The study of persons is broadly chronological. The study of persons more thematic, with a special focus on the Dogmatic Constitution on Divine Revelation. Part Two considers the intersection of person and revelation in the works of each of Hans Urs von Balthasar and David Walsh. Balthasar situates the study theologically; Walsh provides the key philosophical insight into the reality of persons, namely, their simultaneously foundational and evanescent character. These two authors together illustrate how thoroughgoing a personal approach to revelation can be. Part Three considers these findings in relation to Scripture and the Eucharist. In relation to Scripture, the prayer of the Shema, key parts of Chapter 10 of the gospel of St Luke, as well as chapter 17 of the gospel of St John manifest the structure highlighted in Part Two. Finally, the dynamic of the Eucharist crystallises the personal approach to revelation.